Engineering Pseudomonas protegens Pf-5 for nitrogen fixation and its application to improve plant growth under nitrogen-deficient conditions - Setten, Lorena; Soto, Gabriela Cinthia; Mozzicafreddo, Matteo; Fox, Ana Romina; Lisi, Christian Daniel; Cuccioloni, Massimiliano; Angeletti, Mauro; Pagano, Elba Maria; Diaz Paleo, Antonio Horacio; Ayub, Nicolás Daniel (2017)
Nitrogen is the second most critical factor for crop production after water. In this study, the beneficial rhizobacterium Pseudomonas protegens Pf-5 was genetically modified to fix nitrogen using the genes encoding the nitrogenase of Pseudomonas stutzeri A1501 via the X940 cosmid. Pf-5 X940 was able to grow in L medium without nitrogen, displayed high nitrogenase activity and released significant quantities of ammonium to the medium. Pf-5 X940 also showed constitutive expression and enzymatic activity of nitrogenase in ammonium medium or in nitrogen-free medium, suggesting a constitutive nitrogen fixation. Similar to Pseudomonas protegens Pf-5, Pseudomonas putida, Pseudomonas veronii and Pseudomonas taetrolens but not Pseudomonas balearica and Pseudomonas stutzeri transformed with cosmid X940 showed constitutive nitrogenase activity and high ammonium production, suggesting that this phenotype depends on the genome context and that this technology to obtain nitrogen-fixing bacteria is not restricted to Pf-5. Interestingly, inoculation of Arabidopsis, alfalfa, tall fescue and maize with Pf-5 X940 increased the ammonium concentration in soil and plant productivity under nitrogen-deficient conditions. In conclusion, these results open the way to the production of effective recombinant inoculants for nitrogen fixation on a wide range of crops.